PREFACE - A.M. Brazal; R. Pieris (Acta Theologica)
Within the context of the COVID-19 pandemic the 10th Biennial Conference of the Ecclesia of Women in Asia,2 22-26 February 2022, focused on the theme: Toward life-giving communities in a post-pandemic world: Asian feminist theological perspectives. “Life-giving community” is one that is inclusive, communitarian, egalitarian, empowering, and respectful of differences. It is a community that goes beyond the boundaries of gender, class, or race/ethnicity, fostering the right relations with God, other peoples, and creation. This Special Issue is a collection of selected articles from that Conference.